The Effectiveness of U-Shape Seating Arrangement Strategy for Discussion in Speaking Class - Rohdearni Wati Sipayung; Benarita Benarita (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This resaerch is focused on the effectiveness of U-Shape seating arrangement strategy for discussion in speaking class at teh first grade students of SLTP Negeri 2 Pematang Raya. The Problem of this research are: 1) How does the teacher implement U-Shape seating arrangement for discussion in speaking class of the first grade students at SLTP Negeri 2 Pematang Raya? ; 2) Is U-Shape seating arrangement effective for discussion in speaking class of the first grade students at SLTP Negeri 2 Pematang Raya? : 3) What are the students’ responses toward U-Shape seating arrangement for discussion? The objective of this research are: 1) To describe implementation of U-Shape seating arrangement for discussion in speaking class of the first grade students at SLTP Negeri 2 Pematang Raya; 2) To analyze the effectiveness of U-Shape seating arrangement for discussion in speaking class of the first grade students at SLTP Negeri 2 Pematang Raya; 3) To know the students’ responses toward U-Shape seating arrangement for discussion. From the data anaysis it can be concluded that : 1)  The teacher uses her strategy to implement U-shape seating arrangement for discussion in speaking class of the first grade students at SLTP Negeri 2 Pematang Raya. U-shape seating arrangement is effective for discussion due to some proofs. First, U-shape seating arrangement helps the teacher leading the discussion well. The teacher can clearly give instruction to the students, easily monitor the students, and easily interact with the students during discussion in U-shape seating arrangement on the first day  and second day observation; 2) The students show good responses toward U-shape seating arrangement for discussion. 55.56% of number of the students state that they like implementing U-shape seating arrangement for discussion, and 22.22% of number of the student’s state that they like implementing U-shape seating arrangement for discussion very much. Besides, 51.85% of the students state that they feel comfortable with U-shape seating arrangement for discussion, and 33.33% of them state that they feel much comfortable.